Explaining Transborder Terrorist Attacks: The Cases of Boko Haram and Al-Shabaab. Issue 4 (2nd October 2018) - Cannon, Brendon; Iyekekpolo, Wisdom
ABSTRACT: This article demonstrates that transborder attacks by Boko Haram and Al-Shabaab are mainly for rational reasons. Using the Global Terrorism Database, we demonstrate that both groups perform transborder attacks primarily for reactive and rational reasons based on pressure from counterterrorism offensives that resulted in shrinking opportunity spaces within the home state. Concurrently, with the push of the groups towards the periphery of the home states, each group capitalizes on geographically closer opportunity spaces present in neighbouring countries. Our findings also demonstrate that ideological concerns were likely secondary in target selection, thus contradicting a popular but unsubstantiated narrative in terrorism studies.